2019
DOI: 10.1038/s41393-019-0249-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle training in individuals with spinal cord injury: effect of training intensity and -volume on improvements in respiratory muscle strength

Abstract: Study design Retrospective cohort study. Objectives To investigate the effect of training intensity and-volume on improvements in respiratory muscle strength in individuals with spinal cord injury (SCI). Setting SCI rehabilitation center in Switzerland. Methods Inpatients with SCI, lesion level C4-T12, who had at least 10 individualized inspiratory muscle training sessions with respiratory function measurements before and after the training period. Multiple regression analysis with natural logarithmic (ln) tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Furthermore, compared with the non-RMT group, the RMT group showed significant improvements in MIP at 1 month and in tidal volume and RSBI at 6 months. Several recent studies showed that RMT can significantly improve respiratory function based on MIP, MEP, and FVC with 4–12 weeks training [ 54 , 59 , 60 ]. In 67 individuals with SCI at levels C4–T12, Raab et al found that at least 10 individualized inspiratory muscle training sessions produced a 7% increase in MIP and a 6.8% increase in MEP per 10 units of increase in training intensity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compared with the non-RMT group, the RMT group showed significant improvements in MIP at 1 month and in tidal volume and RSBI at 6 months. Several recent studies showed that RMT can significantly improve respiratory function based on MIP, MEP, and FVC with 4–12 weeks training [ 54 , 59 , 60 ]. In 67 individuals with SCI at levels C4–T12, Raab et al found that at least 10 individualized inspiratory muscle training sessions produced a 7% increase in MIP and a 6.8% increase in MEP per 10 units of increase in training intensity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies showed that RMT can significantly improve respiratory function based on MIP, MEP, and FVC with 4–12 weeks training [ 54 , 59 , 60 ]. In 67 individuals with SCI at levels C4–T12, Raab et al found that at least 10 individualized inspiratory muscle training sessions produced a 7% increase in MIP and a 6.8% increase in MEP per 10 units of increase in training intensity [ 59 ]. Shin et al admitted 104 patients with SCI for 4–8 weeks of in-patient clinical rehabilitation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical MST paradigms in the clinic consist of three sessions (with 25–30 repetitions), 3–5 days per week, 4–8 weeks ( Carpinelli and Otto, 1998 ; Schlumberger et al, 2001 ; Rhea et al, 2002 ; Sapienza et al, 2011 ). The intensity of MST can directly affect improvement in respiratory muscle strength ( Raab et al, 2019 ).…”
Section: Methods To Enhance Plasticitymentioning
confidence: 99%
“…There are two main MST strategies: resistance and threshold training. Resistance MST consists of breathing through a small diameter hole, making the participant breathe harder due to the limited airflow ( Sapienza and Wheeler, 2006 ; Berlowitz and Tamplin, 2013 ; Raab et al, 2019 ). It can be targeted toward either inspiratory or expiratory muscles ( Roth et al, 2010 ) or combined ( Kim et al, 2017 ).…”
Section: Methods To Enhance Plasticitymentioning
confidence: 99%
See 1 more Smart Citation